Impact of ferulic acid and resveratrol on the effectiveness and safety of sunscreen - Thamires Batello Freire; Claudinéia Aparecida Sales de Oliveira Pinto; Maria Inês de Almeida Gonçalves; Cristina Helena dos Reis Serra; Michelli Ferrera Dario; André Rolim Baby; Maria Valéria Robles Velasco (Universidade de São Paulo, 2023)
Abstract The combination of avobenzone (AVO) and octyl ρ-methoxycinnamate (OMC) is widely used to ensure broad-spectrum photo-protection because they absorb UVA and UVB, respectively. However, they are thermally and photo unstable because they degrade and undergo photo- tautomerization and trans-cis isomerization, thus reducing their photo-protection efficacy during UV exposure. This study aimed to evaluate the potential use of the antioxidants ferulic acid and resveratrol as stabilizing substances in AVO and OMC mixtures in solution or emulsion. The effects of both antioxidants on the thermal/photo-stability and suppression of the filter singlet state, besides skin permeation, were evaluated. Both antioxidants contributed to preserving OMC and AVO during the thermal stability test, which relates to the maintenance of photo-protection even after storing the formulations at high temperatures. Nevertheless, although resveratrol retained part of the OMC trans isomer and suppressed the AVO singlet state when exposed to UV, no contribution to photo-protection stability was observed, contrary to expectations. Regarding the permeation assay, the addition of both antioxidants was accompanied by a reduction of AVO permeation, while resveratrol increased OMC permeation. Thus, the chemical and physicochemical properties of these antioxidants impacted their efficacy and safety profiles; therefore, further studies are required to establish the real cost-benefit ratio for their use in sunscreens.